Dangguijakyak-san ameliorates memory deficits in ovariectomized mice by upregulating hippocampal estrogen synthesis - Deok-Sang Hwang; Namkwon Kim; Jin Gyu Choi; Hyo Geun Kim; Hocheol Kim; Myung Sook Oh (BMC, 2017)
Abstract Background Dangguijakyak-san (DJS) is an herbal formulation that has been clinically applicable for treating postmenopausal symptoms and neurological disorders. It is reported that hippocampal estrogen attenuates memory impairment via neuroprotection and synaptogenesis. However, the effect of DJS on hippocampal estrogen synthesis remains unknown. In this study, we explored the effect of DJS and its neuroprotective mechanism against memory impairment in ovariectomized (OVX) mice, with respect to hippocampal estrogen stimulation. Methods Cell cultures were prepared from the hippocampi of 18-day-old embryos from timed pregnant Sprague-Dawley rats. The hippocampi were dissected, collected, dissociated, and plated in 60-mm dishes. The cells were treated with DJS for 48 h and the supernatant was collected to determine estrogen levels. Female ICR mice (8-weeks-old) were housed for 1 week and ovariectomy was performed to remove the influence of ovary-synthesized estrogens. Following a 2-week post-surgical recovery period, the mice were administrated with DJS (50 and 100 mg/kg/day, p.o.) or 17β-estradiol (200 μg/kg/day, i.p.) once daily for 21 days. Hippocampal and serum estrogen levels were determined using enzyme-linked immunosorbent assay kit. Memory behavioral tests, western blot, and immunohistochemical analyses were performed to evaluate the neuroprotective effects of DJS in this model. Results DJS treatment promoted estrogen synthesis in primary hippocampal cells and the hippocampus of OVX mice, resulting in the amelioration of OVX-induced memory impairment. Hippocampal estrogen stimulated by DJS treatment contributed to the activation of cAMP response element-binding protein and synaptic protein in OVX mice. Conclusion DJS may attenuate memory deficits in postmenopausal women via hippocampal estrogen synthesis.